“FLEXIBILIDAD COGNITIVA EN LOS ESTUDIANTES DE LA ESCUELA PARTICULAR “JESÚS INFANTE” PERÍODO ACADÉMICO OCTUBRE 2018 MARZO 2019” - Patiño Vivas, Katherine Esthefania (2019)
Cognitive flexibility is the executive process responsible for generating modifications in behaviors and thoughts in dynamic contexts, subject to rapid changes and fluctuations; Therefore, the possibility of changing efficiently and quickly when circumstances demand it is an essential feature of adaptive behavior and adjusted to the objectives (Introzzi & Canet, 2015). A cross-sectional study is presented below because it will be carried out in an established, descriptive period, since it focuses on the phenomenon to be studied, allowing to detail the characteristics of the problem to be investigated, we worked with students of fifth and sixth levels at "Infante Jesus" Private School, the same were evaluated by means of the stroop test. It can be concluded that students have a good cognitive flexibility, it was also determined that within the word scale there is no greater difference between men and women, quite the contrary of the scales color and word-ones where there is evidenced that women have greater cognitive flexibility. Finally, we can recommend that teachers and parents stimulate should stimulate the cognitive flexibility of students, through stretching exercises, physical activity and the daily use of teaching material.